PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN KETERAMPILAN MENULIS PUISI ANAK SISWA KELAS III SD NEGERI 147 PEKANBARU - Herdi Susanto Herdi Susanto; Otang Kurniaman Otang Kurniaman; Gustimal Witri Gustimal Witri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The problem this research is the students writing skills of childrenpoetry third grade students through the learning model SD Negeri 147 PekanbaruContextual Learning Model (CTL). This research subject were students of (III) SD Negeri147 Pekanbaru 2014/2015 school year the were onlyas 35 students. While objects inthis research is to improve the writing skills of children through models poetryContextual Learning Model (CTL). This research was conducted in two cycles, the firstcycle consists of two meetings with one end of a cycle and repeat the second sklus alsoconsists of two cycles consist of two meetings with one cycle replications. The datacollection instruments in this study was the observation sheet teacher and studentobservation sheet and assessment sheet results. The level of students' abilities beforeaction categorized as low to the score with average 62.71. While the value of MasteryMinimum Criteria 70. Among the students who totaled 35 people only 15 people whoreached KKM with the increased about 42.85%. At the first UAS student skill levelsrose by an average increased about 71.02 with both categories. While the skill level ofthe child after the act of writing poetry UAS II with an average increased about 84,30with very good category. The data collection instruments using teacher observationsheets and sheets of observations of students during the learning process were studentsof (III) SD Negeri 147 Pekanbaru, the percentage of teachers in the first cycle ofactivity first meeting of 60.71% with enough categories, at the second meeting of thefirst cycle of 71.42%. Furthermore, the percentage of the second cycle of the firstmeeting of 85.71% with the good category, at the second meeting of the second cycle of92.85%. Furthermore, the activity of the first cycle students first meeting with apercentage of 57,14% sufficiently categories, the second meeting of the first cycle of67.85% with the good category. Furthermore, the second cycle of the first meeting witha good 78.57%, in the second meeting of the second cycle 89.28 with very goodcategory. From the above shows that through Contextual Learning Model Learning (CTL)can increase the skill of writing poetry Indonesian children students of (III) SD Negeri147 Pekanbaru.Key Words : Contextual Learning Model, Students’ Result of writing skills